Motivasi Berprestasi sebagai Mediator Kepuasan Kerja - Mujib, Abdul (Jurnal Psikologi, 2012)
The objective of this study is to examine the influence of work culture and religiosity on job satisfaction through achievement motivation as mediator variable. The subject of this study was 220 civil government lecturers State Islamic University Syarif Hidayatullah Jakarta that spread across 11 faculties by using method of proportional random sampling.Through survey method, this study distributed questionnaires that using aitems response model based on Likert scales, they are job satisfaction scale which consists 14 aitems, achievement motivation scale which consists 14 aitems, work culture which consists 12 aitems, and religiosity scale which consists 14 aitems. Confirmatory factor analysis had been applied to measure validity of the scales, while to test the model used path analysis. This study found that work culture and religiosity have significant positive influence on job satisfaction through achievement motivation. T-value of the influence of achievement motivation on job satisfaction is 4.51 > 1.96 (9% of contribution), work culture on achievement motivation is 3.14 > 1.96 (11.9% of contribution), and religiosity on achievement motivation is 6.25 > 1.96 (15.4% of contribution).This study concluded that a theoretical model of the influences of work culture and religiosity on job satisfaction through achievement motivation among lecturers State Islamic University Syarif Hidayatullah Jakarta is fit; additionally there is a significant and positive relationship between work culture and religiosity through achievement motivation among lecturers State Islamic University Syarif Hidayatullah Jakarta. The study implicates the increment of achievement motivation, work culture and religiosity among lecturers State Islamic University Syarif Hidayatullah Jakarta will be followed by increment of job satisfaction. Keywords: achievement motivation, job satisfaction, path analysis, religiosity, work culture